2011
DOI: 10.1007/s10552-010-9725-0
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and reduced risk of hepatocellular carcinoma: findings from the Singapore Chinese Health Study

Abstract: Background Coffee consumption has been associated with reduced markers of hepatic cell damage, reduced risk of chronic liver disease, and cirrhosis across a variety of populations. Data on the association between coffee consumption and risk of hepatocellular carcinoma (HCC), especially in high-risk populations, are sparse. Methods This study examines the relationship between coffee and caffeine consumption, and the risk of developing HCC within the Singapore Chinese Health Study, a prospective cohort of 63,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 34 publications
4
67
0
1
Order By: Relevance
“…The estimates were similar in Asian (RR = 0.68, 95% CI: 0.57-0.82) and European/American (RR = 0.63, 95% CI: 0.46-0.87) studies, although in the former countries consumption of coffee was generally lower. Sensitivity analysis showed that the overall estimates were slightly modified when we removed in turn the studies of Petrick et al (2015), Johnson et al (2011), andSetiawan et al (2015); however, even after their exclusion from the meta-analysis, the overall estimates remained largely below unity. Further, the restriction of the meta-analysis to studies providing separate estimates for HCC cases, instead of liver cancer, did not materially alter the summary RR (data not shown).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The estimates were similar in Asian (RR = 0.68, 95% CI: 0.57-0.82) and European/American (RR = 0.63, 95% CI: 0.46-0.87) studies, although in the former countries consumption of coffee was generally lower. Sensitivity analysis showed that the overall estimates were slightly modified when we removed in turn the studies of Petrick et al (2015), Johnson et al (2011), andSetiawan et al (2015); however, even after their exclusion from the meta-analysis, the overall estimates remained largely below unity. Further, the restriction of the meta-analysis to studies providing separate estimates for HCC cases, instead of liver cancer, did not materially alter the summary RR (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…When the reported RRs were based on a different reference category, we calculated RR estimates for various levels by dividing each RR by the RR for the lowest category, and the corresponding CIs using the standard errors obtained from published CIs. Given the differences in the intake of coffee among the study population (generally lower in Asian studies), we used different cut-off points between low and high consumption according to the study population: in particular, the cut-off point was three cups per day in seven studies on HCC (Inoue et al, 2005(Inoue et al, , 2009Hu et al, 2008;Johnson et al, 2011;Lai et al, 2013;Petrick et al, 2015;Setiawan et al, 2015) and three studies on CLD (Klatsky et al, 2006;Lai et al, 2013;Setiawan et al, 2015), two cups in one study on CLD (Ruhl and Everhart, 2005a), one cup in four studies on HCC (Kurozawa et al, 2005;Shimazu et al, 2005;Ohishi et al, 2008), and one on CLD (Goh et al, 2014), and 60 and 83 ml of coffee for female and male participants, respectively, in one study on HCC (Bamia et al, 2015). We showed study-specific and summary RRs for regular, low, and high coffee consumption compared to no/occasional consumption using a forest plot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that consumption of coffee may play a protective role against various diseases of modern society, such as obesity, type 2 diabetes, cancer, and cardiovascular disorders (12) as well as neurodegenerative disorders (13,14). More recently, a number of studies have suggested the protective effect of coffee intake and coffee constituents on liver function (15). A growing number of epidemiologic evidence has shown an inverse association between coffee consumption and the risk of NAFLD (16).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between coffee and risk of HCC was studied also by Johnson et al [25] through a large prospective study including 63,257 patients. The authors reported that subjects consuming ≥ 3 cups/day experienced a 44% of HCC risk reduction.…”
Section: Coffeementioning
confidence: 97%